Determining The Probability of Changing Grades from The Mathematical Statistics II Prerequisites Course Using The Markov Chain Process - I Putu Eka Suarsa; Made Novita Dewi; Ni Kade Hindu Pertiwi; Ulfatun Farika Novitasari; Dyan Ayu Wijayanti; I Gusti Ayu Made Srinadi; Made Ayu Dwi Octavanny (Pusat Riset dan Inovasi Nasional, 2024)
Courses are a place for study material that must be studied by students and must be delivered by a lecturer. Courses are an important element in the smallest unit of student learning transactions, which are served by educational institutions to measure their achievement index. The course achievement index is seen based on the value intervals set by the educational institution. Udayana University is one of the educational institutions in Indonesia and is famous in Bali for one of its study programs, namely the mathematics study program which is within the scope of the Faculty of Mathematics and Natural Sciences. The Udayana University Mathematics Study Program has 8 assessment letter scales, namely A, B+, B, C+, C, D+, D, E with the provision that the achievement index for each course is above the letter scale C. One of the purposes of having an achievement index is that it can be used in determine the taking of prerequisite courses for other courses.